INTEGRITAS AKADEMIK TERKAIT KEJUJURAN DANKEADILANANTARA MAHASISWI S-1 PROFESI BIDANDAN S2 ILMU KEBIDANAN - Paramitha, Intan Azkia; Kusumawati, Wiwik; Anjarwati, Anjarwati (UI Scholars Hub, 2023)
Academic integrity is a fundamental value that students must have. This value includes five aspects: honesty, trust, fairness, respect, and responsibility. The purpose of this research was to analyze the difference of academic integrity related to honesty and fairness in the students of Bachelor Midwife Profession and Magister Midwifery Program students at the University ' Aisyiyah Yogyakarta. This research implemented the descriptive-analytic design with a cross-sectional approach. The population of this study was 311 people with samples of 311 people. Samples were taken with total sampling techniques. Data were then analyzed using Chi- Square data analysis. Analysis results showed the existence of significant differences in perception, opinion, behavior, commitment and sanctions of honesty and fairness in the Bachelor Midwife Profession and Magister Midwifery Program students at the University ' Aisyiyah Yogyakarta with a value p for the perception of honesty of 0.010 while the perception of justice is 0.000. The honesty opinion value is 0.001, while justice opinion is 0.002. Honesty behavior is 0.01, while the behavior of justice amounted to 0.03. Honesty commitment is 0.000, while the value of P for the commitment of justice is 0.000. Honesty sanctions value is 0.000 while justice sanctions valued as 0.000. Students are expected to implement integrity behavior since midwifery students do not only encounter with academic duties but also will become health professionals directly communicating with the patient.